Teaching Basic Economics through English in Islamic Higher Education: A Mixed Methods - Wahyuni, Irna; Shalihah, Maratus; Widianita, Rika (El-Rusyd, 2025)
The integration of content and language learning has increasingly been recognized as an effective pedagogical approach to enhance both subject comprehension and foreign language proficiency. This study examines the effectiveness of using English as a medium of instruction in teaching basic economics within an Islamic higher education context to improve students’ understanding of economic concepts and their English language skills. Employing a qualitative descriptive design, the study involved students enrolled in a basic economics course delivered in English. Data were collected through classroom observations, analysis of students’ learning tasks, and questionnaires, and were analyzed thematically. The findings reveal that English-medium instruction fosters active student engagement, enriches discipline-specific economic vocabulary, and strengthens comprehension of fundamental economic concepts. Despite initial challenges related to limited English proficiency, sustained exposure and supportive instructional strategies were found to mitigate these difficulties. The study highlights the potential of English-medium instruction as an effective approach to strengthening the quality and global orientation of economics education in Islamic higher education.